THE EFFECT OF QUIZIZZ APPLICATION IN READING COMPREHENSION TOWARD THE SECOND GRADE STUDENTS AT SMP NEGERI 1 TELLU SIATTINGE - Yulia Udin Safitri; Abidin Pammu; Nasmilah (Bajang Institute, 2022)
This research purposed to investigate some impacts of the Quizizz application in reading comprehension at Junior High School students and selected a quantitative approach by using quasi-experimental method. Nonrandomized experimental group and control group design were applied in this research. Some participants were the second grade students at SMP Negeri 1 Tellu Siattinge. The instrument selected pre-test and post-test in experimental and control groups in the part of reading tests toward students. Then the result appeared the mean score of pre-test in the experimental group was 63.61, and the control group was 63.65. While the mean score of post-test in the experimental group was 82.84, and the post-test of the control group was 75.61. The independent sample t test analysis of post-test from both classes showed the value of significance (2-tailed) was 0.000, while the mean of Sig. (2-tailed) was lower than 0.05. This result showed that H1 was accepted, and H0 was rejected. The researcher inferred that there was an improvement to the ability of students for reading comprehension through Quizizz application.